GAMBARAN KETIDAKLELENGKAPAN PENGISIAN FORMULIR LAPORAN ANESTESI KASUS BEDAH DI RSU IMELDA PEKERJA INDONESIA MEDAN - Valentina; Sri Mulia Melayu (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2020)
Every health service provided to patients must recorded in the medical records completely because the completeness of filling the medical record is used as an indicator of the quality of health services in the hospital. The purpose of this study is to determine the incomplete picture of filling out an anesthetic case report form in a surgical case at the Imelda Indonesian Workers Hospital in Medan. The type of research is descriptive. The populations of this study are all forms of anesthesia patient case reports for the first quarter of 2020 with a total of 728 forms. The samples are 88 forms taken using systematic random sampling. Data collection was carried out using the checklist sheet. Data were analyzed univariate to describe the characteristics of each research variable by producing a frequency distribution and percentage of each variable. The results showed that there were 24 anesthetized report forms that were completely filled and 64 anesthetic report forms that were not completely filled. The highest percentage of incompleteness of filling in the patient identity component on the item date of birth was 10 forms (11%), on the anesthesia time component on the old surgical item by 39 forms (44%), on the diagnostic component on the post-surgical diagnostic item by 28 forms (32%), the examination component on the preoperative state item was 63 forms (72%) and the signature component was 2 forms (2%). It is recommended that every health worker who provides health services to surgical case patients fill out the anesthetic report form in accordance with the SPO authorizing the medical record filling, and to the medical record officer to conduct an assembling or complete analysis of medical record documents.